Routine versus selective use of episiotomy in primigravida: a prospective non-randomized case-control study - Modi, Dipti A.; Vaishnav, Palak P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Episiotomy is a surgically planned incision on the perineum and the posterior vaginal wall during second stage of labour. It is an inflicted second-degree perineal tear. Objective of this study was to determine the possible benefits and risks of the use of selective episiotomy versus routine episiotomy during delivery in primigravida. Methods: This is a prospective non-randomized case-control study designed to analyze and compare the maternal outcomes following routine versus selective use of episiotomy in primigravida. In control group, 122 patients were recruited and mediolateral episiotomy was given in all patients; while in study group, 61 patients were recruited, in whom episiotomy was given selectively. Results: In study group 61 patients were recruited, out of which episiotomy can be avoided in 23 (37.7%) of cases. There was no 3rd or 4th degree perineal tear found in any group. Perineal pain score on 3rd day postpartum was less in study group, as compared to control group on bed rest, sitting, walking and defecation. Conclusions: Selective use of episiotomy can improve maternal outcome by reducing perineal lacerations and those having intact perineum can have the best outcome when episiotomy is given selectively.